THE TEACHERS IMPLEMENTATION DIGITAL GAMES IN TEACHING ENGLISH VOCABULARY - Az-zahra, Fatimah; Sofyan, Ryan Rayhana; Sally, Fauzan Hari Sudding (Universitas Negeri Makassar, 2025)
This research was a qualitative case study aimed at investigating how teachers implement digital games in teaching English vocabulary and how these games impact young learners. The research subjects consisted of one English teacher and 20 fifth-grade students at SD Islam Athirah Bukit Baruga. Data were collected through observation checklists, field notes, interviews, and documentation, and were analyzed using four steps: data collection, data condensation, data display, and conclusion drawing/verification. The findings showed that the teacher implemented the Wordwall digital games systematically, starting from preparation, implementation, to evaluation. The use of Wordwall improved students’ vocabulary retention, participation, and confidence in learning English. Although some students preferred traditional methods such as textbooks, most found game-based learning more enjoyable and easier to understand. Challenges such as differences in student ability and technical issues were overcome through teacher support. Overall, digital games had a positive impact on vocabulary learning for young learners.